2021
DOI: 10.1021/acs.cgd.1c00390
|View full text |Cite
|
Sign up to set email alerts
|

NaCl-Assisted CVD Growth of Large-Area High-Quality Trilayer MoS2 and the Role of the Concentration Boundary Layer

Abstract: Direct growth of wafer scale high quality 2D layered materials (2DLMs) on SiO2/Si substrate is still a challenge. The chemical vapor deposition (CVD) technique has played a significant role in achieving a large area continuous film of 2DLMs. CVD growth requires the optimization of many growth parameters such as temperature, amount of precursors, pressure, carrier gas flow and distance between the reactants. However, the role of boundary layer of reactants concentration has not been explored yet. The amount of … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
22
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 55 publications
2
22
0
Order By: Relevance
“…These controlled experiments reveal that Na 2 CO 3 plays a vital role in establishing the composition and phase state of the carbonization pyrolysis product, and that it has an effect on the phosphatized sample [ 24 ]. To determine the effect of Na 2 CO 3 , the initial solid-state grinding mixture was evaluated by XRD.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These controlled experiments reveal that Na 2 CO 3 plays a vital role in establishing the composition and phase state of the carbonization pyrolysis product, and that it has an effect on the phosphatized sample [ 24 ]. To determine the effect of Na 2 CO 3 , the initial solid-state grinding mixture was evaluated by XRD.…”
Section: Resultsmentioning
confidence: 99%
“…Specifically, NaCl as a template establishes the composition and size of the alloy/metal particles as well as the carbon matrix; meanwhile, NaHCO 3 increases the porous architecture during the carbonization pyrolysis process. Thus, the phosphatized catalyst integrates the merits of having a sufficient number of active sites, thanks to the Ni 5 P 4 /Ni 2 P heterojunction, with an efficient electron/mass transfer capacity thanks to the hierarchically interlaced porous carbon scaffold and the alloy particles [ 24 , 31 ].…”
Section: Resultsmentioning
confidence: 99%
“…As reported in our previous work, a water-soluble layer (Na 2 S/Na 2 SO 4 ) was also grown underneath MoS 2. 42 , 64 The Na 2 S/Na 2 SO 4 layer functions as a seed promoter and supports the nucleation of the large-area, uniform, and continuous MoS 2 film.…”
Section: Experimental Sectionmentioning
confidence: 99%
“…[ 1 ] Inspired by their work, some other materials were also developed based on spin coating. [ 2,3 ] The authors also proposed that this technique can be used to produce functional single crystalline inorganic materials such as semiconductors by further depositing semiconductors on top of the spin‐coated films. [ 1 ] One of the great promises of this proposal is that after the semiconductor depositions, the intermediate sacrificial layer can be removed, and the semiconductor layer can be transferred to another host substrate enabling parent wafer reuse.…”
Section: Introductionmentioning
confidence: 99%
“…[6] Even though NaCl was used as a water-soluble sacrificial layer to successfully fabricate some devices, no functional semiconductor devices were demonstrated. [3,7] Our own study showed that Na + has high diffusivity during subsequent semiconductor growth at elevated temperatures making liftoff challenging after semiconductor deposition.Fluorides, on the other hand, are far less sensitive to moisture and have lower diffusivity during semiconductor deposition. Fluorides can also be lattice engineered to match many semiconductors including Gallium Arsenide (GaAs).…”
mentioning
confidence: 99%